Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Find the implicit derivative $\frac{d}{dx}\left(y=\frac{3}{x}-\frac{2}{x^2}+\frac{2}{3x^3}\right)$

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

undefined

Step-by-step explanation

Problem to solve:

$\frac{d}{dx}\left(y=\frac{3}{x}-\frac{2}{x^2}+\frac{2}{3x^3}\right)$
1

Apply the formula: $\frac{a}{bx}$$=\frac{\frac{a}{b}}{x}$, where $a=2$, $b=3$ and $x=x^3$

$\frac{d}{dx}\left(y=\frac{3}{x}-\frac{2}{x^2}+\frac{\frac{2}{3}}{x^3}\right)$

Unlock this step-by-step solution!

Answer

undefined
$\frac{d}{dx}\left(y=\frac{3}{x}-\frac{2}{x^2}+\frac{2}{3x^3}\right)$

Main topic:

Implicit differentiation

Related formulas:

5. See formulas

Time to solve it:

~ 0.17 seconds

100% Verified Tutors